Theorizing civilian control of the military in emerging democracies: agency, structure and institutional change - Croissant, Aurel; Kühn, David; Chambers, Paul W.; Lorenz, Philip; Wolf, Siegfried O. (Zeitschrift für vergleichende Politikwissenschaft, 2011)
This article integrates insights from historical institutionalism and arguments of strategic action in order to develop a new conceptual and theoretical approach to explaining changes in civil-military relations. In order to enforce civilian control over the military in new democracies, civilian decision-makers need to “break” stabilizing mechanisms of path dependence in civil-military relations. The ability of ‘change agents’ to overcome ‘path dependence’ depends on the concrete approach civilians take to reduce military power. Civilian choices, however, are structured by the specific structural, institutional and ideational contexts in which civil-military interaction takes place. These contextual factors also provide the constraints and resources for civilian actions. The civilian choices and the success of their control strategies are thus conditioned by the resources to which civilians have access and which allow them to initiate and consolidate changes vis-à-vis those actors opposing change in civil-military relations.
Gesehen am 19.03.2021
Keywords: Erde